Water runoff modelling - Biernat, Krzysztof; Pytlak, Joanna (Studia Ecologiae et Bioethicae, 2012)
This article analyzes the process of modelling water runoff, including the phenomena responsible for the modification of the riverbed. First of all, it examines the morphology of rivers and water relations prevailing in the stream. The article also discusses the goals and techniques of [ood control. The article may be the subject of further discussion on the effect of modification of watercourses on the environment.